Long-term Treatment Effects of Lumbar Arthrodeses in Degenerative Disk Disease: A Systematic Review With Meta-Analysis. Issue 9 (November 2015) - Unknown
Abstract : Study Design: Systematic review with meta-analysis. Objective: To (1) evaluate long-term patient-centered clinical outcomes after lumbar arthrodesis with or without decompression for lumbar spondylosis (LS); and (2) compare these outcomes with those of alternative treatments, including nonsurgical and surgical which maintain mobility of the lumbar spine. Summary of Background Data: The effective treatment of LS is a complex clinical and economic concern for patients and health care providers. Methods: Selection criteria: (1) randomized controlled clinical trials (RCTs) comparing treatment effects of lumbar arthrodesis with other interventions; (2) participants: skeletally mature adults with lumbar degenerative disk disease. Search methods: Ovid MEDLINE, Embase, the Cochrane Library, and others. All years through February of 2013 were included. Patient-centered clinical outcomes before treatment, at 12, 24, or >24 months of follow-up, and rate of complications and additional surgical treatment were collected. A meta-analysis was performed to evaluate pooled treatment effects. The GRADE approach was applied to evaluate the level of evidence. Results: The review included 38 studies of 5738 participants. All studies showed strong or at least moderate treatment effects of lumbar arthrodesis at 12, 24, and 48–72 months of follow-up. The level of evidence was moderate at 12 and 24 months, and low at 48–72 months. The pooled long-term treatment effect of lumbar arthrodesis exceeded those of: nonsurgical treatment ( P <0.0001) with a moderate level of evidence, and decompression without fusion ( P =0.005) with a low level of evidence. The treatment effect of lumbar arthrodesis showed a small inferiority versus arthroplasty at 12 and 24 months of follow-up ( P <0.001), but not after 24 months postoperative. Conclusions: This review indicates that surgical stabilization of the lumbar spine is an effective treatment for LS; in particular, for patients with severe chronic low back pain that has been resistant to ≥3 months of conservative therapy.